2008
DOI: 10.3390/ijms9091704
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Carbon-Carbon Multiple Bonds on the Solvolyses of Tertiary Alkyl Halides: a Grunwald-Winstein Analysis

Abstract: Abstract:The influence of carbon-carbon multiple bonds on the solvolyses of 3-chloro-3-methylbutyne (1), 2-chloro-2-phenylpropane (2), 2-bromo-2-methyl-1-phenylpropane (3), 4-chloro-4-methyl-2-pentyne (4) and 2-chloro-2-methylbutane (5) is critically evaluated through the extended Grunwald-Winstein equation. Substrates 1, 3 and 5 lead to correlations with unexpected negative sensitivity, h, to changes in the aromatic ring parameter, I. It is claimed that I is not a pure parameter, reflecting also some solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The specific rates required for the analyses of the specific rates of solvolysis of 3 , 6 , and 18 are from a recent paper by Reis, Elvas-Leitao, and Martins [38] and those for 11 , 12 , 13 , 14 , 15 , 16 , and 17 solvolyses [35] and for 8 [39] and 19 [40] solvolyses from three papers by Takeuchi and co-workers.…”
Section: Application Of Equation 1 To Solvolyses Of Tertiary Alkylmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific rates required for the analyses of the specific rates of solvolysis of 3 , 6 , and 18 are from a recent paper by Reis, Elvas-Leitao, and Martins [38] and those for 11 , 12 , 13 , 14 , 15 , 16 , and 17 solvolyses [35] and for 8 [39] and 19 [40] solvolyses from three papers by Takeuchi and co-workers.…”
Section: Application Of Equation 1 To Solvolyses Of Tertiary Alkylmentioning
confidence: 99%
“…Except for compound 12B , data from a paper by Martins and coworkers [38], the specific rate values are from a publication by Liu and coworkers [42]. They carried out the study using a series of bromides with gradually increasing steric hindrance to nucleophilic attack at the α-carbon.…”
Section: Application Of Equation 1 To Solvolyses Of Tertiary Alkylmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Martins and coworkers [18] applied equation 4 to the specific rates of solvolysis of five moderately-hindered tertiary alkyl halides (substrates mostly with the absence of π-electrons) and found the sensitivities ( h ) to changes in the aromatic-ring parameter ( I ) were sometimes positive and sometimes negative. They suggested that the negative h values arose because I was not a pure parameter and proposed that it included a solvent nucleophilicity component [18].…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the negative h values arose because I was not a pure parameter and proposed that it included a solvent nucleophilicity component [18]. After a thorough analysis of the available specific rates of solvolyses of 30 highly-hindered tertiary alkyl derivatives, we concluded in a recent review [19] that it appears that the apparent utility of the hI term for substrates not having appropriately placed π-electrons is an artifact resulting from moderate multicollinearity that is present between the I values and a linear combination of N T and Y X values.…”
Section: Introductionmentioning
confidence: 99%